Diferentes processos de branqueamento da celulose e seus efeitos nas propriedades físicas e cristalinidade - Marco Antonio Bandeira Azevedo (2011)
The segment of cellulose pulps for the manufacture of tissue paper and printing and writing represents almost all domestic production of bleached Kraft pulp, using eucalyptus wood as raw material almost exclusively, which has excellent quality and high productivity. Theconversion of crystalline to amorphous regions tends to increase water absorption by the fiber, which is favorable for the manufacture of tissue paper. It can also facilitate the refining of the pulp and reduce the cost to manufacture writing papers. This paper conducts a broad survey of the use of six samples of brown pulp Eucalyptus grandis (A), Eucalyptus dunni (B), Eucalyptus urograndis (C), Eucalyptus urograndis with prehydrolysis (G), Pinus taeda (H) and Pinus taeda sulfite (J) as feedstock for the production of bleached pulp, having as main objective the study of crystallinity during the bleaching of pulp. Three bleaching sequences were studied: ODHT(EP)DP as reference sequence, O(ZE)DPa sequence 1 and OPMo(ZE)D sequence 2. The monitoring of changes in the crystalline structure of cellulose was by analysis of X-ray diffraction. The results of oxygen delignification for the various raw materials are consistent with those observed in the literature. It is noticeable an efficiency of delignification from 32% to37.6% for the A, B, C and H pulps, while the G and J pulps which come from pre-hydrolysis pulping and sulfite showed a reduction in the number kappa over 45%. The levels of brightness reversion observed for the three sequences showed similar behavior in all pulps. The lowerreversals were observed in the reference sequence. With the exception of H pulp, pulps consumed 1.1 to 4.8% of total active chlorine. The performance of the H pulp was lower than the other pulps. In addition to increased consumption of total active chlorine, only the referencesequence reached the final brightness of 90% ISO. In this study, the pulps showed no change in the crystalline arrangement when comparingthe different bleaching processes, with values of various indices of crystallinity. This means that different bleaching agents act differently on the cellulose, thus affecting the crystallinity, ie the proportion of crystalline and amorphous regions in cellulosic pulps. Samples A, C, G, H and Jhad higher crystallinity at the end of bleaching in comparison with its brown pulp, except for B pulp where the final crystallinity is lower. The study of thermal decomposition of bleached pulps shows that a relationship exists between the heat of dehydration of the samples of cellulose and its crystallinity index. It was not possible, however, to establish any relationship between the crystallinity index and crystallite size with the stability of cellulose during bleaching. The physical and mechanical properties of C Eucalyptus urograndis pulp were studiedbleached by sequences ODHT(EP)DP, O(ZE)DPa and OPMo(ZE)D. Through the results analyzed in C bleached pulp, the reference sequence (ODHT(EP)DP) was more suitable for the production of printing and writing paper, the sequences 1 and 2 (O(ZE)DPa and OPMo(ZE)D) for theproduction of tissue paper.